Health condition of women with mental disorder - Nadja Cristiane Lappann Botti; SSimone Campos Ferreira; Rafaella Gontijo Nascimento; Jeizziani Aparecida Ferreira Pinto (Universidade Federal do Ceará, 2014)
This research aimed to evaluate the reproductive, gynecological, sexual and clinical aspects of women with mental disorders. This is an exploratory research with quantitative approach performed in a Psychosocial Care Center, Type III, in Divinópolis, Minas Gerais, Brazil, with 39 women with mental disorders. Data collection took place from October to December 2012, through used semi-structured interviews and checked blood pressure, blood glucose, weight and height. The results revealed normal levels of blood pressure and postprandial blood glucose, change in body mass index, presence of menstrual flow, nulliparity, first sexual intercourse in adolescence, early menarche, and lack of climacteric symptoms and history of abortion. Comprehensive health care for women involves more than the demands and needs of the mental health field.